PDL1 Is Required for Peripheral Transplantation Tolerance and Protection from Chronic Allograft Rejection - Tanaka, Katsunori (2007)
The PD-1:PDL pathway plays an important role in regulating alloimmune responses but its role in transplantation tolerance is unknown. We investigated the role of PD-1:PDL costimulatory pathway in peripheral and a well established model of central transplantation tolerance. Early as well as delayed blockade of PDL1 but not PDL2 abrogated tolerance induced by CTLA4Ig in a fully MHC-mismatched cardiac allograft model. Accelerated rejection was associated with a significant increase in the frequency of IFN-γ-producing alloreactive T cells and expansion of effector CD8(+) T cells in the periphery, and a decline in the percentage of Foxp3(+) graft infiltrating cells. Similarly, studies using PDL1/L2-deficient recipients confirmed the results with Ab blockade. Interestingly, while PDL1-deficient donor allografts were accepted by wild-type recipients treated with CTLA4Ig, the grafts developed severe chronic rejection and vasculopathy when compared with wild-type grafts. Finally, in a model of central tolerance induced by mixed allogeneic chimerism, engraftment was not abrogated by PDL1/L2 blockade. These novel data demonstrate the critical role of PDL1 for induction and maintenance of peripheral transplantation tolerance by its ability to alter the balance between pathogenic and regulatory T cells. Expression of PDL1 in donor tissue is critical for prevention of in situ graft pathology and chronic rejection.